2015
DOI: 10.7566/jpsj.84.044712
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Pressure Effect on Superconductivity of BiS2-Based Ce1−xNdxO1−yFyBiS2 and Nd1−zSmzO1−yFyBiS2

Abstract: We have systematically investigated the crystal structure and the magnetic properties of BiS 2 -based superconductor Ce 1-x Nd x O 1-y F y BiS 2 (x = 0 -1.0, y = 0.3 , 0.5 and 0.7) and Nd 1-z Sm z O 1-y F y BiS 2 (x = 0 -0.8, y = 0.3 , 0.5 and 0.7) . In the REOBiS 2 system, both crystal structure and physical properties are tunable by substituting with the different RE (RE = rare earth) elements, having a different ionic radius, such as Ce, Nd and Sm.In the Ce 1-x Nd x O 1-y F y BiS 2 system, bulk superconduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 25 publications
5
51
0
Order By: Relevance
“…T c values estimated from the magnetization measurements are represented with the larger circles in Fig. 1(a), which are in agreement with the results of a previous study [21]. Ce, and Pr, a small portion (smaller than 4%) of REF3 impurity phases was detected, and a two-phase analysis was performed.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…T c values estimated from the magnetization measurements are represented with the larger circles in Fig. 1(a), which are in agreement with the results of a previous study [21]. Ce, and Pr, a small portion (smaller than 4%) of REF3 impurity phases was detected, and a two-phase analysis was performed.…”
supporting
confidence: 89%
“…As reported in Ref. 21, bulk superconductivity of REO0.5F0.5BiS2 appears at an RE 3+ -radius of ~113 pm, which corresponds to RE = Pr or Ce0.5Nd0.5. Tc increases with the decrease of the RE 3+ radius.…”
supporting
confidence: 64%
“…Although it was reported that SmO 0.5 F 0.5 BiS 2 can be synthesized by solid state reaction, 33 this result might be helpful in explaining why this parent com- pound could not be synthesized in other studies using the same method. 27,31 As is shown in Fig. 6, ρ(T) of La 1−x Sm x O 0.5 F 0.5 BiS 2 increases with decreasing temperature at low pressures in their normal state, indicating semiconducting-like behavior, which is suppressed by applied pressure.…”
Section: Resultsmentioning
confidence: 76%
“…Although the value of T c for x = 0.8 is the highest among the four compositions at ambient pressure, dT c /dP is negative with a value of roughly -0.45 K/GPa, which results in a decreasing T c with pressure down to P t o . These results suggest that reduction of the lattice parameter a, which is regarded to be essential to the enhancement of T c for BiS 2 -based compounds at ambient pressure, 11,27,31,32 does not always result in an increase of T c .…”
Section: Resultsmentioning
confidence: 89%
“…A few groups have been able to perform partial elementsubstitutions in the LnO block layers (Ln = La, Ce, and Nd) in LnO 1−x FxBiS 2 superconductors [47][48][49][50][51]. First, the results corresponding to samples with x = 0.5 are discussed.…”
Section: Isovalent Substitution At Block Layersmentioning
confidence: 99%